Practicing Ethics Harmony Ethics and Martial Arts - Mendoza, Perseville (Philippine Social Sciences Review; Vol 62 No 1: January-June 2010, Ed. Eric Manalastas, 2011)
It is undeniable that knowledge of various ethical theories, no matter how extensive, is insufficient when it comes to the question of actual ethical living. The former does not guarantee the observance of said theories, and admittedly, nowhere do these theories claim to have the capacity to do so. Thus, the problem of the existence of a chasm between theory and practice remains. The author believes that ethical living has to come from within an individual, imposed as it were, by the individual upon the self, in order to actualize an ethical society. However, the question of whether virtue can be taught also lingers in the background. The answer seems to lie in personal subjugation to a form-al practice. This is possible through actual training in ethical living, and it is argued that an individual can be trained in actualizing virtuous action by way of training in budo or traditional martial arts. The main purpose of the presentation is to offer a perspective of the traditional martial arts as a practical and viable ethical alternative, based on the premise that training in martial arts is actually training in ethical living by the very nature of its practice, given specific recommendations. It paves the way for an ethics of self-care comparable to that of the Greeks, as it develops in a martial artist a “disciplined”, hence ethical, self.
Keywords: ethics, martial arts